Repetitive somatic embryogenesis induced cytological and proteomic changes in embryogenic lines of Pseudotsuga menziesii [Mirb.] - Gautier, Florian; Eliášová, Kateřina; Leplé, Jean-Charles; Vondráková, Zuzana; Lomenech, Anne-Marie; Le Metté, Claire; Label, Philippe; Costa, Guy; Trontin, Jean-François; Teyssier, Caroline; Lelu-Walter, Marie-Anne (BMC plant biology, 2018)
BACKGROUND: To explore poorly understood differences between primary and subsequent somatic embryogenic lines of plants, we induced secondary (2ry) and tertiary (3ry) lines from cotyledonary somatic embryos (SEs) of two Douglas-fir genotypes: SD4 and TD17. The 2ry lines exhibited significantly higher embryogenic potential (SE yields) than the 1ry lines initiated from zygotic embryos (SD4, 2155 vs 477; TD17, 240 vs 29 g- 1 f.w.). Moreover, we observed similar differences in yield between 2ry and 3ry lines of SD4 (2400 vs 3921 g- 1 f.w.). To elucidate reasons for differences in embryogenic potential induced by repetitive somatic embryogenesis we then compared 2ry vs 1ry and 2ry vs 3ry lines at histo-cytological (using LC-MS/MS) and proteomic levels. RESULTS: Repetitive somatic embryogenesis dramatically improved the proliferating lines' cellular organization (genotype SD4's most strongly). Frequencies of singulated, bipolar SEs and compact polyembryogenic centers with elongated suspensors and apparently cleavable embryonal heads increased in 2ry and (even more) 3ry lines. Among 2300-2500 identified proteins, 162 and 228 were classified significantly differentially expressed between 2ry vs 1ry and 3ry vs 2ry lines, respectively, with special emphasis on "Proteolysis" and "Catabolic process" Gene Ontology categories. Strikingly, most of the significant proteins (> 70%) were down-regulated in 2ry relative to 1ry lines, but up-regulated in 3ry relative to 2ry lines, revealing a down-up pattern of expression. GO category enrichment analyses highlighted the opposite adjustments of global protein patterns, particularly for processes involved in chitin catabolism, lignin and L-phenylalanine metabolism, phenylpropanoid biosynthesis, oxidation-reduction, and response to karrikin. Sub-Network Enrichment Analyses highlighted interactions between significant proteins and both plant growth regulators and secondary metabolites after first (especially jasmonic acid, flavonoids) and second (especially salicylic acid, abscisic acid, lignin) embryogenesis cycles. Protein networks established after each induction affected the same "Plant development" and "Defense response" biological processes, but most strongly after the third cycle, which could explain the top embryogenic performance of 3ry lines. CONCLUSIONS: This first report of cellular and molecular changes after repetitive somatic embryogenesis in conifers shows that each cycle enhanced the structure and singularization of EMs through modulation of growth regulator pathways, thereby improving the lines' embryogenic status.
Keywords: Douglas-fir; Proteomic; Plant Somatic Embryogenesis Techniques; Seeds; semena rostlinná; genové regulační sítě; Plant Proteins; proteomika; somatická embryogeneze rostlin; Proliferation; Gene Regulatory Networks; hmotnostní spektrometrie; rostlinné proteiny; Embryogenic potential; Proteomics; Pseudotsuga; Cytology; Mass Spectrometry; Plant growth regulators